2019
DOI: 10.1159/000502950
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Impairment Is Associated with Absolute Intraoperative Frontal α-Band Power but Not with Baseline α-Band Power: A Pilot Study

Abstract: Background: Cognitive abilities decline with aging, leading to a higher risk for the development of postoperative delirium or postoperative neurocognitive disorders after general anesthesia. Since frontal α-band power is known to be highly correlated with cognitive function in general, we

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 41 publications
3
31
0
2
Order By: Relevance
“…The association between low alpha-band and cognitive impairment are consistent with recent work from Koch and colleagues (Koch et al, 2019). The analysis of the average AP effect (average marginal effect Figure 2A) showed a significant association with CD.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The association between low alpha-band and cognitive impairment are consistent with recent work from Koch and colleagues (Koch et al, 2019). The analysis of the average AP effect (average marginal effect Figure 2A) showed a significant association with CD.…”
Section: Discussionsupporting
confidence: 90%
“…Some authors proposed a new complementary use of peroperative EEG aimed at predicting CD, or even more generally peri operative neurocognitive disorder, using patterns such as the intra operative Burst Suppression (BS) (Wildes et al, 2019). Recently, the decrease of power spectral density in the alpha band (8-13Hz), collected on the frontal EEG under general anesthesia has been associated not only to chronological age but also to preoperative CD (Koch et al, 2019). On the other hand, it is also recognized that the effective dosage of hypnotics under general anesthesia decreases with age (Schnider model and MAC) but also with preoperative cognitive status (Laalou et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Ein weiterer Risikofaktor für das Auftreten eines postoperativen Delirs v. a. bei älteren Patienten sind präoperative kognitive Einschränkungen [25]. Diese sind ebenfalls mit einer geringeren intraoperativen α-Power assoziiert [35,36].Wie bereits erwähnt, führt das Auftreten eines postoperativen Delirs wiederum zu einem erhöhten Risiko für langanhaltende postoperative kognitive Defizite [26]. Eine EEG-gesteuerte Narkose kann das Risiko für das Auftreten dieser Langzeitfolgen verringern [24,37].…”
Section: Reduktion Von Postoperativen Kognitiven Defizitenunclassified
“…Eine EEG-gesteuerte Narkose kann das Risiko für das Auftreten dieser Langzeitfolgen verringern [24,37]. Auch bei Patienten mit präoperativen kognitiven Einschränkungen zeigt sich eine intraoperativ geringere α-Power [25,35,36], was auch hier den Einfluss einer prädisponierenden Vulnerabilität bestätigt.…”
Section: Reduktion Von Postoperativen Kognitiven Defizitenunclassified
“…Postoperative delirium is a common complication in older surgical patients and has been associated with increased length of stay, functional decline, and increased 1 year postoperative mortality rates. 1-3 Recent guidelines call for 1,4 or at least encourage 5,6 EEG-based anesthetic management to reduce delirium rates, and intraoperative anesthetized raw EEG features such as burst suppression and alpha band power have been associated with postoperative delirium 7-10 and preoperative cognitive impairment, 11,12 respectively. Fritz et al demonstrated that increased anesthetic sensitivity (as indicated by EEG burst suppression at lower anesthetic dosage) is associated with increased postoperative delirium risk.…”
Section: Introductionmentioning
confidence: 99%